Android Based WI-FI Controlled Robot using Raspberry Pi - Gulesci, Mehmetcan; Orhun, Murat (IEEE, 2017)
This paper shows a way to control a robot using Raspberry Pi and application built in the Android Platform. The purpose of this paper is to control the robot as upward, backward, right or left side and get a live video stream on Android phone from USB Cam by using Raspberry Pi. The Android phone and Raspberry Pi hoard is connected through WI-FI. As designed, the Android application is the command control center for the robot. The signals which is generated from Android app are sent to Raspberry pi and Raspberry pi receives these signals according to a program written in the python programming language in Raspberry pi. So the commands are processed and the robot is directed with user directive.
2017 International Conference on Computer Science and Engineering (UBMK) -- OCT 05-08, 2017 -- Antalya, TURKEY
Keywords: Robotic Car; Raspberry Pi; Wı-Fı; Android